Agrobacterium-mediated Transformation of Vitis Cv. Monastrell Suspension-Cultured Cells: Determination of Critical Parameters - Chu, Mingyu; Quinonero, Carmen; Akdemir, Hulya; Alburquerque, Nuria; Angeles Pedreno, Maria; Burgos, Lorenzo (Wiley, 2016)
Although some works have explored the transformation of differentiated, embryogenic suspension-cultured cells (SCC) to produce transgenic grapevine plants, to our knowledge this is one of the first reports on the efficient transformation of dedifferentiated Vitis vinifera cv Monastrell SCC. This protocol has been developed using the sonication-assisted Agrobacterium-mediated transformation (SAAT) method. A construct harboring the selectable nptII and the eyfp/IV2 marker genes was used in the study and transformation efficiencies reached over 50 independent transformed SCC per gram of infected cells. Best results were obtained when cells were infected at the exponential phase. A high density plating (500 mg/dish) gave significantly better results. As selective agent, kanamycin was inefficient for the selection of Monastrell transformed SCC since wild type cells were almost insensitive to this antibiotic whereas application of paromomycin resulted in very effective selection. Selected eyfp-expressing microcalli were grown until enough tissue was available to scale up a new transgenic SCC. These transgenic SCC lines were evaluated molecularly and phenotypically demonstrating the presence and integration of both transgenes, the absence of Agrobacterium contamination and the ability of the transformed SCC to grow in highly selective liquid medium. The methodology described here opens the possibility of improving the production of valuable metabolites. (C) 2016 American Institute of Chemical Engineers Biotechnol.
Keywords: eyfp; nptII; paromomycin; plating density; SAAT